Alkalinization in the Isolated and Perfused Anterior Midgut of the Larval Mosquito, Aedes aegypti - Onken, Horst (University of Wisconsin Library, 2008)

(untitled)
In the present study, isolated midguts of larval Aedes aegypti L. (Diptera: Culicidae) were mounted on perfusion pipettes and bathed in high buffer mosquito saline. With low buffer perfusion saline, containing m-cresol purple, transepithelial voltage was monitored and luminal alkalinization became visible through color changes of m-cresol purple after perfusion stop. Lumen negative voltage and alkalinization depended on metabolic energy and were stimulated in the presence of serotonin (0.2 µmol l(-1)). In some experiments a pH microelectrode in the lumen recorded pH values up to 10 within minutes after perfusion stop. The V-ATPase inhibitor concanamycin (50 µmol l(-1)) on the hemolymph side almost abolished V(te) and inhibited luminal alkalinization. The carbonic anhydrase inhibitor, methazolamide (50 µmol l(-1)), on either the luminal or hemolymph-side, or the inhibitor of anion transport, DIDS (1 mmol l(-1)) on the luminal side, had no effect on V(te) or alkalinization. Cl(-) substitution in the lumen or on both sides of the tissue affected V(te), but the color change of m-cresol purple was unchanged from control conditions. Hemolymph-side Na(+) substitution or addition of the Na(+)/H(+) exchange inhibitor, amiloride (200 µmol l(-1)), reduced V(te) and luminal alkalinization. Luminal amiloride (200 µmol l(-1)) was without effects on V(te) or alkalinization. High K(+) (60 mmol l(-1)) in the lumen reduced V(te) without affecting alkalinization. These results indicate that strong luminal alkalinization in isolated and perfused anterior midgut of larval A. aegypti depends on basolateral V-ATPase, but is apparently independent of carbonic anhydrase, apical Cl(-)/HCO(3)(-) exchange or apical K(+)/2H(+) antiport.